PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PT. PERKEBUNAN NUSANTARA - BUSTANUL ARIFIN, MOCH (Jurnal Akuntansi AKUNESA, 2017)
This study aims to examine and analyze the effect of financial ratios to financial distress at PT. Perkebunan Nusantara. Financial ratios are measured by liquidity ratio, activity ratio, profitability ratio and leverage ratio, while financial distress is measured by Z-Score. This study used a sample of 13 companies from a total of 14 PT. Perkebunan Nusantara during the study period 2012-2016. Data were analyzed using logistic regression analysis method. This study found that 11 companies of PT. Perkebunan Nusantara experiencing financial distress and two other companies are not experiencing financial distress that PTPN 4 and 10. In addition, it was found that the ratio of liquidity negatively affect financial distress while activity ratios, profitability ratios and the leverage ratio does not affect the financial distress.